2006
DOI: 10.1111/j.1365-2427.2006.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish community changes after minimum flow increase: testing quantitative predictions in the Rhône River at Pierre‐Bénite, France

Abstract: 1. Many aspects of the flow regime influence the structure of stream communities, among which the minimum discharge left in rivers has received particular attention. However, instream habitat models predicting the ecological impacts of discharge management often lack biological validation and spatial generality, particularly for large rivers with many fish species. 2. The minimum flow at Pierre-Bénite, a reach of the Rhô ne river bypassed by artificial channels, was increased from 10 to 100 m 3 s )1 in August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 29 publications
2
60
0
Order By: Relevance
“…The LIFE scores (Lotic-invertebrate Index for Flow Evaluation; Extence et al, 1999) were clearly related to two major droughts recorded within the study period, demonstrating the impact of low-flow events on stream communities. In another recent study involving biological validation, Lamouroux et al (2006) measured a significant change in the structure of a fish community after the artificial increase of the minimum flow in a reach of the Rhône River (France).…”
Section: Discussionmentioning
confidence: 99%
“…The LIFE scores (Lotic-invertebrate Index for Flow Evaluation; Extence et al, 1999) were clearly related to two major droughts recorded within the study period, demonstrating the impact of low-flow events on stream communities. In another recent study involving biological validation, Lamouroux et al (2006) measured a significant change in the structure of a fish community after the artificial increase of the minimum flow in a reach of the Rhône River (France).…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods are difficult to apply to existing hydropower installations (Biggs and Jowett, 2007); some authors have shown that the entire range of discharges is not always necessary for the restoration of a viable salmonid population (Jowett and Biggs, 2006). To advance the discussion, one would need data built up over the long term, related to the hydrological regime of the installation or to experimental modification of plant management modes (Studley et al, 1995;Capra et al, 2003;Souchon et al, 2007); such experimentation has so far been unfortunately too rare (Bayley, 2002;Jowett and Biggs, 2006;Lamouroux et al, 2006;Sabaton et al, 2008). However, some methods of quantifying fish habitat as a function of discharge have indeed been developed (Milhous, 1979;Stalnaker, 1979;Bovee, 1982;Souchon et al, 1989;Sabaton et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Results from the available long-term hydroecological studies indicate that instream communities are influenced by variations in both the climatological (Bradley and Ormerod, 2001;Daufresne et al, 2003;Scarsbrook et al, 2003) and hydrological regimes (e.g., Lamouroux et al, 2006;Monk et al, 2006, Scarsbrook, 2002Wagner and Schmidt, 2004;Wood et al, 2001). However, attempts to quantify macroinvertebrate community response to river flow variability, and in particular high and low flows, are currently limited in terms of their temporal (typically <5 years study period) and/or geographical coverage (e.g., Caruso 2002;Clausen and Biggs, 1997;Sheldon and Thoms, 2006;Suren and Jowett, 2006).…”
Section: Introductionmentioning
confidence: 99%